PERILAKU PEMADATAN TANAH EKSPANSIF DI BAWAH STANDAR MAXIMUM DRY DENSITY (MDD): (Studi Kasus Susteran Marcederia, Oesusu, Kecamatan Takari, Kabupaten Kupang) (Eternitas: Jurnal Teknik Sipil, 2025)
Abstract: Expansive soils experience significant volume changes due to water content fluctuations, threatening structural stability. Soil compaction reduces porosity and increases dry density, improving mechanical properties. This study evaluates the effect of compaction below Maximum Dry Density (MDD) at 95%, 90%, and 85% on physical and mechanical properties of expansive soil in Kupang. Methods include water content, dry density, California Bearing Ratio (CBR), and direct shear tests. Results indicate that reduced compaction increases water content and porosity, decreases dry density and CBR. Cohesion increases while internal friction angle decreases, indicating reduced soil stability. This study emphasizes the importance of achieving MDD to ensure structural reliability on expansive soils.
Keywords: tanah ekspansif; pemadatan; maximum dry density; CBR; kuat geser